2017
DOI: 10.1111/adb.12599
|View full text |Cite
|
Sign up to set email alerts
|

Rich club and reward network connectivity as endophenotypes for alcohol dependence: a diffusion tensor imaging study

Abstract: We aimed to examine the whole-brain white matter connectivity and local topology of reward system nodes in patients with alcohol use disorder (AUD) and unaffected siblings, relative to healthy comparison individuals. Diffusion-weighted magnetic resonance imaging scans were acquired from 18 patients with AUD, 15 unaffected siblings of AUD patients and 15 healthy controls. Structural networks were examined using network-based statistic and connectomic analysis. Connectomic analysis showed a significant ordered d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
4
16
0
Order By: Relevance
“…The current results are the first to provide a brain-based factor indicative of future drinking in this model, suggesting that premorbid alcohol-naïve differences in Rich Club characteristics of functional brain networks also predict future drinking in this model. These results extend recent findings in human participants demonstrating that white matter brain networks of individuals with AUD displayed lower Rich Club characteristics compared to their non-abusing siblings, who displayed lower levels compared to control participants 44 . While Zorlu, Capraz, Oztekin, Bagci, Di Biase, Zalesky, Gelal, Bora, Durmaz, Besiroglu, Saricicek 44 suggest potential premorbid differences in white matter network structure may be a marker of risk or susceptibility to AUD, the results of the current study provide direct empirical support for this hypothesis, showing that Rich Club characteristics of premorbid functional brain networks are directly related to future drinking levels.…”
Section: Discussionsupporting
confidence: 89%
“…The current results are the first to provide a brain-based factor indicative of future drinking in this model, suggesting that premorbid alcohol-naïve differences in Rich Club characteristics of functional brain networks also predict future drinking in this model. These results extend recent findings in human participants demonstrating that white matter brain networks of individuals with AUD displayed lower Rich Club characteristics compared to their non-abusing siblings, who displayed lower levels compared to control participants 44 . While Zorlu, Capraz, Oztekin, Bagci, Di Biase, Zalesky, Gelal, Bora, Durmaz, Besiroglu, Saricicek 44 suggest potential premorbid differences in white matter network structure may be a marker of risk or susceptibility to AUD, the results of the current study provide direct empirical support for this hypothesis, showing that Rich Club characteristics of premorbid functional brain networks are directly related to future drinking levels.…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that alterations in these hubs or interconnections could likely lead to severe impairments because of their roles in whole‐brain integrative processes (van den Heuvel and Sporns, ). For instance, abnormal rich club organization has been reported in structural connectivity analysis of patients with AUD (Zorlu et al., ). The differences seen here may represent a network phenotype associated with a predisposition to develop AUD.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 1 other structural connectivity study used graph theory analyses in AUD and demonstrated that the AUD group had significantly weaker connectivity, primarily in the right hemisphere (Zorlu et al., ). The edges or tracts of significance included connections of the putamen and hippocampus with other brain regions (Zorlu et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the community index indicates which community or modularity a given node belongs to. Changes in the community index generally suggest the changes of locally connected clusters or modules implicated in specialized information processing (43). Both of these were used to describe the location and efficiency of nodes in the information transfer.…”
Section: Discussionmentioning
confidence: 99%